Application of SAVI Learning Model to Improve Physics Learning Activities with Phet Simulations - Nisa, Narita Ainun; Khumaedi, Khumaedi; Fianti, Fianti (Universitas Negeri Semarang, 2024)
The learning model that is used in the learning process had an impact on the ability of students to analyze problems. The aim of this study was to use the SAVI learning model to increase the analytical student activity in physics in the second grade of senior high school. This study's design was quasi-experimental. This study used this research is purposive sampling because both schools have the same competency level. The data was collected through observation, tests, and documentation. The research was conducted in Jepara with control and experimental groups respectively. The data's validity is evaluated using normality and homogeneity tests. The observation sheet for assessing learning activities has a validation score of 4.39, which is considered very good. The results were proved by observation sheets of student activities, which showed that this strategy was more effective. The experimental group's score increased from 81.94 to 87.92, while the control group's score increased from 79.43 to 81.83. The test scores for the experimental and control groups were 84.93 and 80.62, respectively, indicating that SAVI learning model in this study was found to be effective in improving students' learning activities.